1979
DOI: 10.1085/jgp.73.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Ionic mechanisms of two types of on-center bipolar cells in the carp retina. I. The responses to central illumination.

Abstract: A B $ T R A C T Properties of the depolarizing response of on-center bipolar cells to a light spot stimulus were studied in the carp retina. On-center bipolar cells were classified into two types, cone-dominant and rod-dominant, according to their major input from cones and rods. Cone-dominant bipolar cells responded to spectral light with the maximum amplitude near 625 nm, suggesting major input from red cones. The response was accompanied by a resistance increase and showed a reversal potential at -63 -+ 21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
61
0
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(67 citation statements)
references
References 13 publications
5
61
0
1
Order By: Relevance
“…This negative shift places the activation range of the Ca2+ current within the physiological operating range of on-type bipolar neurons of goldfish retina. In the dark, the resting potential of these cells in situ is -40 to -50 mV (Saito, Kondo & Toyoda, 1979;Kaneko, Famiglietti & Tachibana, 1979), which is near the level at which Ca2+ current began to activate in our voltage-clamp experiments. In response to light, large-terminal on-bipolar neurons depolarize by 10-20 mV (Saito, Kujiraoka & Yonaha, 1983), bringing the potential into the range in which the Ca2+ current increased rapidly with depolarization (e.g.…”
Section: Discussionmentioning
confidence: 57%
“…This negative shift places the activation range of the Ca2+ current within the physiological operating range of on-type bipolar neurons of goldfish retina. In the dark, the resting potential of these cells in situ is -40 to -50 mV (Saito, Kondo & Toyoda, 1979;Kaneko, Famiglietti & Tachibana, 1979), which is near the level at which Ca2+ current began to activate in our voltage-clamp experiments. In response to light, large-terminal on-bipolar neurons depolarize by 10-20 mV (Saito, Kujiraoka & Yonaha, 1983), bringing the potential into the range in which the Ca2+ current increased rapidly with depolarization (e.g.…”
Section: Discussionmentioning
confidence: 57%
“…In this retina, as in the retinas of other lower vertebrates, most classes of ON bipolar cells collect input from both rods and cones. Early studies of the light responses of carp and goldfish retina demonstrated that in these mixed input bipolar cells, light responses arising from rods were associated with a positive reversal potential and a conductance increase, while the light responses originating from cones reversed at negative voltages and were associated with a conductance decrease (Saito et al, 1978;Saito et al, 1979). Note that both conductance mechanisms are functionally similar in that they result in membrane depolarization.…”
Section: Some On Bipolar Cells Signal Through Alternative Mechanismsmentioning
confidence: 99%
“…Since light decreases the input resistance of the bipolar cell, it was argued that the effect of the transmitter was to close ionic channels (Kaneko, 1971;Toyoda, 1973;Saito, Kondo & Toyoda, 1979;Ashmore & Falk, 1980a). The reversal potential Er for depolarizing bipolar cells of the dogfish retina was about -8 mV (Ashmore & Falk, 1980a).…”
Section: Equivalent Circuit Of the Bipolar Cellmentioning
confidence: 99%